A highly sensitive nanobody-based immunoassay detecting SARS-CoV-2 nucleocapsid protein using all-recombinant reagents - Segovia-de los Santos, Paula; Padula-Roca, Carolina; Simon, Ximena; Echaides, Cesar; Lassabe, Gabriel; Gonzalez-Sapienza, Gualberto (Frontiers in Immunology, 2023)
Antigen tests have been crucial for managing the COVID-19 pandemic by identifying individuals infected with SARS-CoV-2. This remains true even after immunity has been widely attained through natural infection and vaccination, since it only provides moderate protection against transmission and is highly permeable to the emergence of new virus variants. For this reason, the widespread availability of diagnostic methods is essential for health systems to manage outbreaks effectively. In this work, we generated nanobodies to the virus nucleocapsid protein (NP) and after an affinityguided selection identified a nanobody pair that allowed for the detection of NP at sub-ng/mL levels in a colorimetric two-site ELISA, demonstrating high diagnostic value with clinical samples. We further modified the assay by using a nanobody-NanoLuc luciferase chimeric tracer, resulting in increased sensitivity (detection limit = 61 pg/mL) and remarkable improvement in diagnostic performance. The luminescent assay was finally evaluated using 115 nasopharyngeal swab samples. Receiver Operating Characteristic (ROC) curve analysis revealed a sensitivity of 78.7% (95% confidence interval: 64.3%-89.3%) and specificity of 100.0% (95% confidence interval: 94.7%-100.0%). The test allows the parallel analysis of a large number of untreated samples, and fulfills our goal of producing a recombinant reagent-based test that can be reproduced at low cost by other laboratories with recombinant expression capabilities, aiding to build diagnostic capacity.